2019
DOI: 10.3126/njms.v4i1.24122
|View full text |Cite
|
Sign up to set email alerts
|

CT guided lung biopsy: Diagnostic yield and complications, using 18G coaxial semi-automatic core needle

Abstract: Introduction: CT guided biopsy is essential for histopathological diagnosis of suspicious lung nodule, which are not amenable for either bronchoscopic or sonography guided sampling. Methods: Twenty eight patients with suspicious lung nodules not amenable for bronchoscopic or sonography guided sampling who underwent CT guided lung biopsy with 18 G coaxial semiautomatic core biopsy needle in one year were retrospectively studied for diagnostic yield and complications. Results: Out of 28 patients, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
1
1
Order By: Relevance
“…They also showed higher parenchymal haemorrhage among all the complications as in our study. 11 Similar finding was also seen in the study done by Thapa et al 8 However, Jumpei and Yuan et al found pneumothorax as the most common complication. 9,10 Wang et al also found significant correlation of parenchymal haemorrhage with diameter of lesion and length of needle within the lung parenchyma, which was not seen in our study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…They also showed higher parenchymal haemorrhage among all the complications as in our study. 11 Similar finding was also seen in the study done by Thapa et al 8 However, Jumpei and Yuan et al found pneumothorax as the most common complication. 9,10 Wang et al also found significant correlation of parenchymal haemorrhage with diameter of lesion and length of needle within the lung parenchyma, which was not seen in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Diagnostic yield of CT guided lung biopsy is high as supported by the studies done by Thapa et al (92.3%), and Jumpei et al (92.9%). 8,9 Yuan et al even had higher diagnostic yield than our study (94.8%). 10 The samples not yielding diagnosis in our study were either necrosis or fibrosis.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Lung biopsy is a reliable procedure performed to inform treatment strategy for patients with abnormal findings of the lung. Cytology of biopsy specimens has long been a major diagnostic modality for initial evaluation of patients with lung cancer (1,2) .…”
Section: Introductionmentioning
confidence: 99%